Pengaruh Film Dokumenter Nada Nusantara Terhadap Kesadaran Siswa Smk Dalam Pelestarian Budaya Lokal (Survei Terhadap Siswa Kelas XI SMKN 10 Bandung) - Syafiqoh, Salwa; Hidayat, Dasrun (UNIVED PRESS, Universitas Dehasen Bengkulu, 2024)
Indonesia's local cultural diversity plays an important role in the country's identity as the world's largest archipelago. The Ministry of Education and Culture records more than 67,273 cultural heritages, including immovable objects, movable objects, and intangible heritages. This diversity requires attention and preservation, especially from the younger generation as cultural successors. Public awareness, especially the younger generation, is very important in preventing the extinction of local culture in the midst of globalization. Mass media, especially documentary films, are considered an effective means to raise this awareness. This study examines the influence of the documentary film